1984
DOI: 10.1103/physrevlett.53.1739
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Raman Sidescatter and Hot-Electron Production in Laser-Plasma Interaction Experiments

Abstract: These experiments studied the Raman instability occurring at densities below the quartercritical density of the incident 0.53-ju,m laser light. Solid gold targets were irradiated by up to 4 kJ of energy in a 1-ns pulse with focal spots of 150 to 1880 /xm. The angular distribution of the Raman scattering shows efficient Raman sidescatter. The energy in electron plasma waves accounts for the hot-electron production over almost three orders of magnitude. We report the results and discuss the implications for lase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0
1

Year Published

1986
1986
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(37 citation statements)
references
References 13 publications
1
35
0
1
Order By: Relevance
“…SRS entails the decay of a laser light wave into an electron plasma wave and a scatteredlight wave at densities at or below one quarter of the critical density of the laser, while TPD is the decay of a laser light wave into two electrostatic plasma waves (plasmons) near the quartercritical density. Previous studies of SRS and TPD have examined single-beam thresholds, 9,10 quantified suprathermal electron production, 6,11,12 explored collective multibeam processes, [13][14][15][16][17][18] and investigated the spatial properties of TPD 19 and the angular distribution of the resulting hot electrons 20 -an important consideration when computing preheat. SRS imposes serious constraints on ignition designs in the indirect-drive approach to ICF because of the high single-beam intensities and large volumes of quasi-homogeneous plasma that are required when using gas-filled hohlraums.…”
mentioning
confidence: 99%
“…SRS entails the decay of a laser light wave into an electron plasma wave and a scatteredlight wave at densities at or below one quarter of the critical density of the laser, while TPD is the decay of a laser light wave into two electrostatic plasma waves (plasmons) near the quartercritical density. Previous studies of SRS and TPD have examined single-beam thresholds, 9,10 quantified suprathermal electron production, 6,11,12 explored collective multibeam processes, [13][14][15][16][17][18] and investigated the spatial properties of TPD 19 and the angular distribution of the resulting hot electrons 20 -an important consideration when computing preheat. SRS imposes serious constraints on ignition designs in the indirect-drive approach to ICF because of the high single-beam intensities and large volumes of quasi-homogeneous plasma that are required when using gas-filled hohlraums.…”
mentioning
confidence: 99%
“…Drake et al 495 used the much larger energy available on the Novette laser (up to 4 kJ) to irradiate Au targets at 0.53-lm wavelength with focal spots of 150-to 1880-lm diameter. They integrated the angular distribution of the SRS to obtain the Raman-scattered light fraction and found that this correlated very closely over nearly three orders of magnitude with the hot-electron fraction obtained from the hard x-ray spectrum ( Fig.…”
Section: Stimulated Raman Scattering (Srs)mentioning
confidence: 99%
“…Another is due to the decay of an EPW into an ion acoustic wave ͑IAW͒ and daughter EPWs as a result of modulational instability of EPWs. [3][4][5] Both have been observed in the damping of the EPW excited by Raman backscattering instability ͑which is a slow-phase-velocity wave͒, [6][7][8] and the latter have been observed in the collinear laser-beat-wave ͑which is a fast-phase-velocity wave͒. 9,10 The damping of a self-modulated laser wakefield was attributed to electron beam loading by Tzeng et al 11 in studies using a particle-in-cell simulation that assumes immobile ions.…”
Section: Introductionmentioning
confidence: 99%